Partisipasi Masyarakat pada Kegiatan Pembuatan Gazebo di Area Kampus 1 Universitas Negeri Gorontalo - Syafriyani Syafriyani; Niniek Pratiwi; M. Ikhsan Rahmat Datuage (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The construction of a gazebo on the grounds of the Rectorate Building at Campus 1 of Gorontalo State University is an integral component of the Building Design Studio I course, which bridges theoretical knowledge and practical application for vocational students. This study aims to explore the process of student involvement in the design, implementation, and completion of the gazebo project, as well as to assess its alignment with the theory of simple building design and construction. The methods used for this project included on-site design evaluations, selection of local materials, distribution of group tasks, site analysis, creation of technical drawings, phased construction involving the lower, middle, and upper structures, and finishing. The results indicate that students effectively translated their technical drawings into a functional and aesthetically appealing structure. The gazebo was built using locally sourced materials, such as wood and bamboo, ensuring the structure met necessary strength standards while blending harmoniously with the campus environment. The activity highlighted the relevance of theoretical knowledge, with discussions emphasizing key concepts such as sustainability, accuracy in measurement, and effective team coordination. Furthermore, students' active participation in the project significantly enhanced their technical and managerial competencies, fostering a sense of responsibility toward the maintenance and development of campus facilities. The hands-on nature of the project also allowed students to gain real-world experience in construction practices, which directly contributes to their vocational training. This project serves as an effective example of project-based learning in vocational education, combining practical skills development with theoretical understanding. By engaging in this real-world application, students were able to strengthen their problem-solving abilities and gain insights into the complexities of construction projects, ultimately preparing them for professional careers in the field of architecture and building design